The course of COVID-19 in newborns - Yu. A. Pavlenko (Журнал инфектологии)
Clinical Infectious Diseases Hospital. S.P. Botkin has been providing assistance to pregnant women and newborns suffering from COVID-19 since the beginning of the pandemic. In the period from April 2020 to April 2022, 550 newborns born to mothers suffering from COVID-19 of varying severity were observed in the hospital, of which 52 children had a registered diagnosis of COVID-19 (the SARS-CoV-2 virus was identified in a swab from the nasopharynx of a newborn using PCR). In this paper, an analysis of the pathological changes identified in this category of newborns was carried out, the issues of the influence of the covid status of the mother and the duration of stay with her on the child’s condition were studied. Analysis of the results of the work revealed a relationship between the duration of the period of stay of a newborn with a mother with an active form of COVID-19 and the severity of the disease in newborns. According to our clinical observations, the vertical route of transmission of the virus seems highly probable. Newborns who have had COVID-19 or have perinatal contact with SARS-CoV-2 are subject to dynamic observation. It is necessary to determine the order, timing and scope of dispensary observation for the timely detection of pathological changes in this category of children.